Analysis on the Key Parameters of Aerospace Microminiaturization Decelerator - Xiangyang Jin; Jianyuan Feng; Lili Zhao (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
A high efficiency special transmission decelerator is designed by scheme design, structural design, optimization design, and return difference analysis and computer simulation. Small teeth difference transmission with the first level bevel gear pair and the second level beveloid gear pair is adopted as the form of transmission in the decelerating system. Great torque and big bending moment are available by transmission ratio formula deduction, force analysis and strength analysis. The particle swarm optimization and the genetic algorithm have been combined and the mutation operator optimization model has been proposed to optimize the design of decelerator. Then the transmission with large transmission ratio, high torque, high power and high precision will be realized in small space. This model has solved the problems of particle swarm optimization in mechanical design. For example, there are more variables, it is constrained and it is easily precocious. This model has provided the theoretical basis for the optimum design of microminiaturization gear system. DOI: http://dx.doi.org/10.11591/telkomnika.v11i10.3399